Tracking Reaction Pathways by a Modular Flow Reactor Coupled to Electrospray Ionization Mass Spectrometry. Issue 10 (21st August 2021) - Tripodi, Guilherme L.; Derks, Max T. G. M.; Rutjes, Floris P. J. T.; Roithová, Jana
Abstract: Reaction monitoring by electrospray ionization mass spectrometry (ESI‐MS) is a popular method for investigation of reaction mechanisms. Here, we present a new approach based on a coupling between a modular capillary flow reactor and ESI‐MS. The flow reactor allows a sequential adding of the reactants. We demonstrate the approach for oxidation of Ph2 S by ArIO catalyzed by [(TPA)Fe(TfO)2 ] (ArIO=2‐( t BuSO2 )C6 H4 IO, TPA=tris(2‐pyridylmethyl)amine, TfO − =triflate). In steps, we could follow the formation of the reactive iron(IV)oxo complexes, then the oxygen transfer reaction from the iron(IV)oxo to the sulfide, and finally the reoxidation of the iron complexes. The flow reactor also allows kinetic experiments by changing relative concentrations of the reactants. We could analyze in detail the formation of various [(TPA)Fe IV O(X)] 2+/+ complexes (X=MeCN, ArI, ArIO, TfO − ) and compare their relative reactivity with Ph2 S. The [(TPA)Fe IV O(MeCN)] 2+ complex is the most reactive complex for the oxygen atom transfer reaction whilst [(TPA)Fe IV O(ArIO)] 2+ prevails in solution under catalytic conditions. Abstract : Flow chemistry with mass spectrometry detection allows qualitative assessment of reaction kinetics of reactive species in solution. The paper shows how reaction pathways in a catalytic cycle can be tracked and how the kinetics of the individual transformations can be studied. The approach is shown for oxygen‐transfer reactions mediated by reactive iron(IV)oxo intermediates.